Postcolonial Issues and Colonial Closures: Portrayals of Ambivalence in Shaun Tan’s The Arrival - Renata Lucena Dalmaso; Thayse Madella (Ilha do Desterro)
This article aims to investigate the visual representation of the connection between immigration and the construction of an Australian identity as a nation in Shaun Tan’s graphic novel The Arrival (2006). Based on the debate about imagined communities and the ambivalence on the narration of a nation, proposed by Benedict Anderson and Homi Bhabha, we will discuss how The Arrival creates moments for the appearance of the ambivalence of cultural difference at the same time that it also constructs a horizontal imagined community. On these terms, The Arrival depicts some of the liminal positionality that immigrants have to deal when they arrive in a new place, but also constructs a cohesive and homogeneous narrative that entails the assimilation of the immigrants. In other words, this work offers a closure that can be read as an assimilation of the colonial discourse for a series post-colonial issues.